THU0009 Reduced Clinical Improvement in Rheumatoid Arthritis Patients Showing IgG1 Allotype -Infliximab Incompatibility. (23rd January 2014) - Montes, A.; Perez-Pampin, E.; Navarro-Sarabia, F.; Moreira, V.; Rodríguez de la Serna, A.; Magallanes, B.; Vasilopoulos, Y.; Sarafidou, T.; Fernández-Nebro, A.; Ordóñez, M. D. C.; Narváez, J.; Cañete, J. D.; et al.
Abstract : Background: IgG1 allotypes (G1m) can induce antibodies in incompatible individuals. Allotypes 1 and 17 are always in the same IgG1 molecule, allotype 2 only appears in IgG1 with allotypes G1m1, 17 but it is not present in all the G1m1, 17 IgG1s. On the contrary, allotype G1m3 is never in the same IgG1 as the other three allotypes. Infliximab (INF) and Adalimumab (ADM) bear the G1m1, 17 allotypes and therefore, they are potentially immunogenic for G1m3 homozygous patients. However, no anti-allotype antibodies were detected in patients treated with ADM in a recent report 1 . Objectives: To assess response to INF and ADM stratified by IgG1 allotype compatibility. Methods: Discovery group was made of 206 patients with RA of Spanish ancestry treated with INF (73.3 %) or ADM (26.7 %). Replication group included 404 patients with RA of the UK (359) and Greece (45) treated with INF (49.3 %) or ADM (50.7 %). Disease activity measured by DAS28 was evaluated at baseline and 3, 6 and 12 months in the discovery group and at baseline and 6 months in the replication group. IgG1 allotypes were identified at the DNA level by minisequencing of two discriminating poylmorphisms. Analyses included linear regression of change in DAS28 from baseline and logistic regression of EULAR response criteria (responder/non-responder). Covariates were baseline DAS28, gender and biologic. Results: Carriers of the G1m17 allotypes were more often responders than non-carriers at 6 months in the discovery group: 39.1 % responders vs . 27.6 % in the incompatible patients, and 18.5 % non-responders in the compatible patients vs . 28.7 % in the incompatible ones (P = 0.048). Also, compatible patients showed more improvement in DAS28 at 6 months than the incompatible ones (2.4 vs . 1.7, P = 0.02). Stratification showed a significant difference in DAS28 change only in patients treated with INF (P = 0.03). Analysis of the replication group confirmed the results in patients treated with INF; responders (22.4 %) and non-responders (7.8 %) in compatible patients, and responders (9.6 %) and no-responders ( 12.05 %) in incompatible patients with p = 0.03). Also, there was larger improvement in DAS28 in compatible than in incompatible patients (DAS28 = 2.6 vs . 2.2, p = 0.02). Conclusions: We have found association between clinical response to INF and compatibility of IgG1 allotypes in RA patients. These results suggest that INF administered to incompatible patients can induce anti-allotype antibodies interfering with treatment. An explanation for the difference between INF and ADM requires further studies. References: Bartelds GM et al. Arthritis Res Ther. 2010;12:R221 Acknowledgements: Members of Biologics in Rheumatoid Arthritis Genetics and Genomics Study Syndicate (BRAGGSS) for their contribution. Funding was provided by grants PI11/01048, PI12/01909 and by RETICS Program, RD08/0075 (RIER) of the Instituto de Salud Carlos III (Spain) that are partially financed by the European Regional Development Fund of the European Union. Disclosure of Interest: None Declared